Correlation between Candida albicans biofilm formation and invasion of the invertebrate host Galleria mellonella. (February 2014) - Borghi, Elisa; Romagnoli, Solange; Fuchs, Beth Burgwyn; Cirasola, Daniela; Perdoni, Federica; Tosi, Delfina; Braidotti, Paola; Bulfamante, Gaetano; Morace, Giulia; Mylonakis, Eleftherios
ABSTRACT: : Aim: The aim of our study was to investigate whether biofilm production by Candida albicans clinical isolates could be a hallmark of virulence in vivo .Materials & methods: Twenty clinical isolates of C. albicans were examined via histological studies on larvae infected with various fungal doses (from 10 3 to 10 5 CFU/larva) of biofilm producer and nonproducer strains.Results: The poor prognostic role of infection due to a biofilm-producing isolate was confirmed by the Wald test (hazard ratio: 2.63; 95% CI: 2.03–3.41). Histological examinations at 24 h showed a strong innate immune response, with evidence of melanization for both infection groups. However, at 48 h, we found huge differences in filamentation and tissue invasion capability between biofilm nonproducing and producing isolates, the latter being highly organized into biofilm and invading the larval intestinal tract. Invasion corroborated survival data.Conclusion: The histological results demonstrate that the production of biofilm could enhance the invasiveness of C. albicans .